Balloon Catheters Versus Vaginal Prostaglandins for Labour Induction (CPI Collaborative): An Individual Participant Data Meta-analysis of Randomised Controlled Trials. Issue 5 (May 2023) - Jones, Madeleine N.; Palmer, Kirsten R.; Pathirana, Maleesa M.; Cecatti, Jose Guilherme; Moraes Filho, Olimpio B.; Marions, Lena; Edlund, Måns; Prager, Martina; Pennell, Craig; Dickinson, Jan E.; Sass, Nelson; Jozwiak, Marta; et al.
ABSTRACT: Since 2010, the rates of induction have risen in Australia (from 25% to 35%) and the United Kingdom (from 20% to 32%). This may be an indication that induction has become more acceptable among women and health providers. In women with unripe cervices, mechanical methods, such as balloon catheters, and pharmacological methods, such as vaginal prostaglandins, are commonly used for cervical ripening to induce labor. Yet, induction poses the risks of cesarean delivery (CD), as well as maternal and neonatal morbidity and mortality. Finding the optimal method to induce labor is important to reduce these risks. The aim of this study was to compare the safety and effectiveness of balloon catheters and vaginal prostaglandins for the induction of labor. This was a meta-analysis using individual patient data from published and unpublished randomized controlled trials that had completed data collection between March 19, 2019, and May 1, 2021. A recent Cochrane review provided additional trials completed before March 19. Eligible trials were those that compared single- or double-balloon catheters with the vaginal prostaglandins, misoprostol, or dinoprostone. The analysis included only women with viable, singleton pregnancies with no exclusion for parity or membrane status. The primary outcomes were CD, a composite of adverse maternal outcomes, and a composite of adverse perinatal outcomes. A total of 12 trials, representing 5460 deliveries, were included in the analysis. Overall, the crude incidence of CD was 27%, the perinatal composite was 13.6%, and the maternal composite was 22.7%. No significant differences in the rate of CD were found between patients who received a balloon catheter and those given vaginal prostaglandin to induce labor (12 trials, 5414 women; adjusted odds ratio [aOR], 1.09; 95% confidence interval [CI], 0.95–1.24). The adverse perinatal composite was lower among those who received balloon catheters (10 trials, 4452 neonates; aOR, 0.80 [95% CI, 0.70–0.92]; I 2 = 0%). There were no significant differences for the adverse maternal composite measure (10 trials, 4326 women; aOR, 1.02 [95% CI, 0.89–1.18]; I 2 = 0%). Balloon catheters were associated with fewer instrumental vaginal births than vaginal prostaglandins (10 trials, 4888 women; aOR, 0.82 [95% CI, 0.68–1.00]). In a subgroup analysis, there was a lower chance of the adverse perinatal composite with the use of a single-balloon catheter versus vaginal prostaglandins (9 trials, 2683 neonates; aOR, 0.84 [95% CI, 0.71–0.99]). This study found that labor induction with balloon catheters and vaginal prostaglandins was equally effective and had similar rates of CD and adverse composite maternal outcome. However, induction with a balloon catheter was observed to improve perinatal outcomes.